Political morality of liberal democracy - Perry, Michael J. (Delhi, 2010)
In this important new work in political and constitutional theory, Michael J. Perry elaborates and defends an account of the political morality of liberal democracy: the moral convictions and commitments that in a liberal democracy should govern decisions about what laws to enact and what policies to pursue. The fundamental questions addressed in this book concern (1) the grounding, (2) the content, (3) the implications for one or another moral controversy and (4) the judicial enforcement of the political morality of liberal democracy. The particular issues discussed include whether government may ban pre-viability abortion, whether government may refuse to extend the benefit of law to same-sex couples and what role religion should play in the politics and law of a liberal democracy.
Keywords: Democracy-Moral and ethical aspects